UTILIZATION OF PAPAYA LEAVES (Carica papaya L.) TO CONTROL ONION PEST SPODOPTERA EXIGUA (LEPIDOPTERA: NOCTUIDAE)LEPIDOPTERA (NOCTUIDAE) - Muhammad Agung Permadi; Rafiqah Amanda Lubis; Syawaludin Syawaludin; Nova Suryani Pasaribu (Universitas Medan Area, 2020)
Spodoptera exigua is a migrant pest that attacks onions simultaneously in groups. The utilization of papaya leaves to control pests due to papaya leaves have toxic compounds that can kill pests. This study aims to measure the ability of papaya leaves to control S. exigua larvae. This research was conducted using a completely randomized design (CRD) experimental method with two treatment factors. The first factor was papaya leaf concentration (0 g / l, 30 g / l, 70 g / l, 100 g / l, 120 g / l), and the second factor is a mixture of kerosene. The treatment was repeated three times. The study was conducted at the Agrotechnology Laboratory, Agriculture Faculty Muhammadiyah University, South Tapanuli. The results showed that papaya leaves could kill S. exigua larvae. The highest mortality of S. exigua worms There were statistically significant non-treatments among treatments.